Optimal potföyün seçimi ve İMKB gıda sektörü üzerinde bir uygulama - Ermek, Özlem (My University, 2004)
Portföy teorisi, finansın klasik sorunlarından biridir. Optimal portföyün ne olduğu, buna nasıl ulaşıldığı hem de kurumsal yatırımcılar için oldukça ilginç bir problemdir. Bu projenin temel amacı, Markowitz'in portföy teorisinin İMKB Gıda sektöründe uygulanabilirliğinin test edilmesi ve minimum riskli ve risk-getiri ilişkisine göre optimum porföyü oluşturmaktır. Bu çalışmanın diğer bir amacı ise, İMKB' nın,gelişmiş ülkelerin borsaları ile karşılaştırılmasıdır. Markowitz'in geliştirdiği portföy teorisi, araştırmacılar ve yatırımcılar için oldukça yol gösterici olmuştur. Markowitz'in porföy analizi yaklaşımı, bütün yatırımcıların riskten kaçındıkları üzerine kurulmuştur. Bunun anlamı, yüksek getiri elde etmek için, yüksek riske katlanılması gerektiğidir. Bu nedenle ytırımcılar, risk ve beklenti düzeylerine dikkat etmelidirler. Bu çalışmada markowitz'in açık ve kesin bir dille koyduğu kuralları uygulandı. İMKB gıda sektörü hisselerinin 2003 yılı günlük kapaniş verileri alındı. Korelasyon ve kovaryanslar hesaplandı. Temel hesaplamalar yapıldıktan sonra eşit ağırlıklı portföy bulundu. Bu bölümden sonra bilgisayar yardımıyla, farklı ağırlıkta portföyler düzenlendi. Yapılan hesaplamalar sonucunda, portföy teorisi ile İMKB Gıda Endeksi' nde yatırımcıların risk katlanma derecelerine göre, minimum riskli ve optimum portföylerin oluşturulabileceği bulundu. Son olarak, bu çalışma daha fazla hisse senediyle daha geniş bir zaman aralığında da uygulanabilr. Bu analiz, çalışılacak zaman aralığı arttırıldığında yatırımcılara daha fazla bilgi sağlayacaktır. One of the classic questions of finance is portfolio theory. Given a set of available assets, i.e. given their prices and the (subjective) distribution of their payoffs, what is the optimal portfolio for one to hold? This is obviously an interesting problem, to individuals as well as to academics. The main purpose of this project is to test the applicability of the Markowitz portfolio theory to Istanbul Stock Exchange (ISE) Food-Beverage Index and creating minimum risky portfolio and optimum portfolio according to the risk and return relationship. One of the other purpose of the study is ISE’s relatively young background with less portfolio studies been conducted comparing with the developed countries stock exchanges. When portfolio theory is conducted, Markowitz and his portfolio theory is the primary guideline for the investors or researchers. Markowitz approach to portfolio analysis is that investors are basically risk-averse. This means simply that investors must be compensated with higher return in order to accept higher risk, so that investors are tending to form portfolios to diversify their risks. Markowitz’s explicit and disciplined processes are used in this study. ISE Food-Beverage Index shares’ 2003 daily closing data’s are taken. The correlations and the covariance’s are calculated as base preparations and equally weighted portfolio is found. After this stage, the different weight sets are formed for each portfolio types with the help of the computer. At the end of the calculations, it is found that the portfolio theory is applicable to ISE Food-Beverage Index and individuals can form their minimum risky portfolios and optimum portfolios according to their risk aversion degree. As a recommendation, this study can be expanded thru more shares and consisting much time. It is sure that expanded time and number of shares will give more options to investors to create less risky and high return portfolios.
Keywords: Ekonomi; Finansman ekonomisi; Portföy Yönetimi; Sermaye